Glial Cell Line-Derived Neurotrophic Factor Induces Barrier Function of Endothelial Cells Forming the Blood–Brain Barrier - Igarashi, Yo; Utsumi, Hiroyuki; Chiba, Hideki; Yamada-Sasamori, Yumiko; Tobioka, Hirotoshi; Kamimura, Yasuhiro; Furuuchi, Ken; Kokai, Yasuo; Nakagawa, Takashi; Mori, Michio; Sawada, Norimasa (Biochemical and biophysical research communications, 1999)
Since a deep involvement of astrocytes, a kind of glial cells, in differentiation of the blood–brain barrier (BBB) has been suggested, we examined the relation of glial cell line-derived neurotrophic factor (GDNF) to the BBB. First, immunohistochemical examination of the cerebral cortex of rats revealed that glial cell line-derived neurotrophic factor receptor (GFRα1) was preferentially expressed on the cell membranes of capillary endothelial cells. Second, to elucidate the effects of GDNF on the BBB, capillary endothelial cells isolated from the porcine cerebral cortex were cultured and then changes in tight junction function of the endothelial cells were examined after addition of GDNF, in terms of transendothelial electrical resistance (TER) and permeability. GDNF at concentrations of 0.1 and 1 ng/ml significantly activated the barrier function of the endothelial cells in the presence of cAMP. Since GDNF is secreted from astrocytes sheathing capillary endothelial cells in the brain cortex, our results strongly suggest that GDNF enhances the barrier function of tight junctions of the BBB on the one hand, and also supports the survival of neurons on the other hand.